The manifest association structure of the single-factor model: insights from partial correlations - Salgueiro, M. F.; Smith, P. W. F.; McDonald, J. W. (Psychometrika, 2008)
The association structure between manifest variables arising from the single-factor model is investigated using partial correlations. The additional insights to the practitioner provided by partial correlations for detecting a single-factor model are discussed. The parameter space for the partial correlations is presented, as are the patterns of signs in a matrix containing the partial correlations that are not compatible with a single-factor model.